Director Networks and Credit Ratings. Issue 2 (2nd April 2018) - Benson, Bradley W.; Iyer, Subramanian Rama; Kemper, Kristopher J.; Zhao, Jing
Abstract: We explore the effect of director social capital, directors with large and influential networks, on credit ratings. Using a sample of 11, 172 firm‐year observations from 1999 to 2011, we find that larger board networks are associated with higher credit ratings than both firm financial data and probabilities of default predict. Near‐investment grade firms improve their forward‐looking ratings when their board is more connected. Last, we find that larger director networks are more beneficial during recessions, and times of increased financial uncertainty. Our results are robust to controls for endogeneity. Tests confirm that causality runs from connected boards to credit ratings.